@anon
sign up
@anon
sign up
pull down to refresh
100 sats
\
1 reply
\
@SimpleStacker
16 Oct 2024
\
parent
\
on: [Daily puzzle] log of a sum and sum of logs
science
Or any combination of 1, 2, and 3.
You get it because:
\log(a) + \log(b) + \log(c) = \log(abc)
Thus, the equation is the same as:
a + b + c = abc
, with
a, b, c > 0
write
preview
reply
100 sats
0 sats
hot
recent
top
0 sats
\
0 replies
\
@0xbitcoiner
16 Oct 2024
👍
reply
\log(a) + \log(b) + \log(c) = \log(abc)
a + b + c = abc
, witha, b, c > 0